A Review: Comparative Analysis of various Data Mining Techniques - Sagar, Pinki; Goyal, Monika (International Journal of Computer Sciences and Engineering, 2025)
Data mining (sometimes called data or knowledge discovery) is the process of analyzing data from different perspectives and summarizing it into useful information – making it more accurate, reliable, efficient and beneficial. In data mining various techniques are used- classification, clustering, regression, association mining. These techniques can be used on various types of data; it may be stream data, one dimensional, two dimensional or multi-dimensional data. In this paper we analyze the data mining techniques based on various parameters. All data mining techniques used for prediction, extraction of useful data from a large data base. Each of the techniques have different performance and result .